2016
DOI: 10.1007/s40858-016-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

ISSR primers for analysis of genetic variability of Stenocarpella maydis

Abstract: Although stalk and ear rot is a major disease affecting corn plants, little is known regarding the genetic variability of Stenocarpella maydis, its main causal agent. In this study, we evaluated inter-simple sequence repeat (ISSR) primers for analysis of genetic variability of the pathogen. For DNA analysis, six isolates of S. maydis were amplified using 42 ISSR primers. Polymorphic information content (PIC), marker index (MI), and resolving power (RP) were calculated for all primers. Of the 42 primers, 50 % s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The same comparison above applied to the F. graminearum population evaluated in our study also showed the high polymorphism of this species in the studied region. Polymorphism levels are important information when working with dominant markers because they are one of the parameters that can be used to indicate genetic variability (Fedrigo et al 2016;Rosa et al 2017;Mariano et al 2019). The high polymorphism observed in the populations of F. graminearum, F. meridionale, and F. austroamericanum in southern Brazil implies high genetic variability in these species; thus, presenting a high adaptative potential.…”
Section: Discussionmentioning
confidence: 99%
“…The same comparison above applied to the F. graminearum population evaluated in our study also showed the high polymorphism of this species in the studied region. Polymorphism levels are important information when working with dominant markers because they are one of the parameters that can be used to indicate genetic variability (Fedrigo et al 2016;Rosa et al 2017;Mariano et al 2019). The high polymorphism observed in the populations of F. graminearum, F. meridionale, and F. austroamericanum in southern Brazil implies high genetic variability in these species; thus, presenting a high adaptative potential.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of primers can only be considered effective when the primers selected to differentiate a species show similar results to those obtained using all available primers (Fedrigo et al, 2016). Typically, in a genetic variability study, a high number of primers is used, consequently increasing the costs and time to obtain results.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PIC and RP indexes has been effective in the selection of primers in several species, such as Jathopha curcas (Tatikonda et al, 2009; Grativol et al, 2011), Ipomoea batatas (Camargo et al, 2013), Stenocarpella maydis (Fedrigo et al., 2016), and Achyrocline flaccida (Rosa et al., 2017). Our work shows that the PIC and RP indexes successfully selected ISSR primer in apple, since the average similarity between the genotypes was the same (0.37) when using the nine selected primers and all 26 polymorphic primers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…flaccida . Additionally, when there is no previous knowledge of microsatellite regions for the genome of the species, ISSR (inter-simple sequence repeat) markers can also be used as an alternative [ 20 23 ]. The ISSR markers have the advantage of analyzing multiple loci in a single polymerase chain reaction (PCR); in addition, they are very informative, reliable, and produce a high level of polymorphism [ 24 ].…”
Section: Introductionmentioning
confidence: 99%